Association between breast cancer risk factors and blood microbiome in patients with breast cancer - Jeongshin An; Hyungju Kwon; Se-Young Oh; Young Ju Kim (Scientific Reports, 2025)
Abstract This study investigated the relationship between risk factors for breast cancer (BC) and the microbiome by comparing the microbiomes of BC patients with fatty liver disease to those with a normal liver. Bacterial extracellular vesicles were collected from each blood sample, and next-generation sequencing was performed. The analysis identified specific microbiome profiles shared among groups with hyperglycaemia, hyperlipidaemia, and high body mass index (BMI), which were then compared with functional biomarkers. In particular, the genus Faecalibacterium was a specific bacterium found in the groups with high concentrations of low-density lipoprotein cholesterol, high BMI, and fatty liver disease. Therefore, when the prognosis of patients with BC was analysed based on Faecalibacterium presence, it was confirmed that patients’ prognoses tended to deteriorate. In this study, BC risk factors, such as hyperglycaemia, hyperlipidaemia, fatty liver, and high BMI, were interconnected through the microbiome. This provides insights into how the risk factors for BC are linked and their impact on the microbiome and human health.